2003
DOI: 10.1207/s15327035ex1104_4
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia Computer-Based Instruction to Teach Students With Moderate Intellectual Disabilities to Use a Debit Card to Make Purchases

Abstract: This study investigated the effectiveness of a multimedia program (interactive computer program, video captions, and still photographs) to teach 3 students with moderate intellectual disabilities to make purchases using a debit card and an automated payment machine (APM). A multiple probe design across participants was used to evaluate the effectiveness of the multimedia program. All instructional sessions occurred through simulations using video captions and still photographs replicating operation of the APM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 22 publications
2
74
0
1
Order By: Relevance
“…Video has also been presented through multimedia computerbased programs to teach functional, multistep tasks, such as the use of a debit card for purchasing (Mechling, Gast, & Barthold, 2003), self-help skills (Hagiwara & Myles, 1999), and grocery shopping . While studies using a VCR have relied on instructor control of the prompting device, computerbased programs allow branching to different screens or video segments in response to student selections on the computer screen.…”
mentioning
confidence: 99%
“…Video has also been presented through multimedia computerbased programs to teach functional, multistep tasks, such as the use of a debit card for purchasing (Mechling, Gast, & Barthold, 2003), self-help skills (Hagiwara & Myles, 1999), and grocery shopping . While studies using a VCR have relied on instructor control of the prompting device, computerbased programs allow branching to different screens or video segments in response to student selections on the computer screen.…”
mentioning
confidence: 99%
“…This form of simulation offers multiple teaching examples that replicate the varied environments in which the skills will be used. In a number of recent studies, researchers have evaluated the use of CBVI in teaching functional community skills, including grocery shopping (Mechling, 2004;Mechling, Gast, & Langone, 2002); shopping in convenience stores (Wissick, Lloyd, & Kinzie, 1992); purchasing with the "next dollar strategy" (Ayres & Langone, 2002) or a debit card (Mechling, Gast, & Barthold, 2003); and verbally ordering at fast-food restaurants (Mechling, Pridgen, & Cronin, 2005). Given statistics indicating that one out of every four adult Americans eats in a fast-food restaurant every day, the ability to access such establishments that serve inexpensive food on the run is considered functional for consumers, including individuals with disabilities (Koorland & Cooke, 1990;Snell & Brown, 2000;Westling & Fox, 2000).…”
mentioning
confidence: 99%
“…As a result, it has been found that CAVI is effective in enabling students to read signs indicating the location of the items in the grocery stores. Mechling, Gast and Barthold (2010) have taught students with moderate intellectual disabilities to use debit cards with CAVI. In the study, the effects of multimedia programs (interactive computer programs, videos, and photos) were examined and videos and photographs about ATM transactions were created.…”
Section: Tartışma Ve Sonuçmentioning
confidence: 99%